Bilateral vocal fold immobility: diagnosis and treatment - Pinto,José Antonio (2011)
Vocal fold immobility may be due to bilateral neurogenic paralysis, cricoarytenoid joint fixation, laryngeal synechiae, or posterior glottic stenosis. Treatment aims to establish a patent airway and preserve the function of the glottic sphincter and voice quality. OBJETIVES: To analyze the diagnostic and therapeutic approaches in cases of bilateral vocal fold immobility seen at our unit. MATERIALS AND METHODS: A retrospective study of 35 patient registries at our unit with a diagnosis of bilateral vocal fold immobility; the etiology and treatment results were evaluated. RESULTS: Among the patients, 18 (51.4%) were cases of bilateral vocal fold palsy, and 17 (48,6%) were cases of posterior glottic stenosis. Patients with bilateral palsy underwent unilateral subtotal arytenoidectomy, and patients with stenosis were treated with the microtrapdoor flap technique, subtotal arytenoidectomy, and/or posterior cricoidotomy (Rethi). CONCLUSION: Bilateral vocal fold immobility is a potentially fatal condition; it is essential to differentiate vocal fold palsy from fixation to choose the appropriate treatment. Subtotal arytenoidectomy with microscopy is our surgery of choice for treating bilateral paralysis; the technique for treating stenosis depends on the amount of stenosis.